COVID-19: Financial Stress Test for Academic Medical Centers. (August 2020) - Colenda, Christopher C.; Applegate, William B.; Reifler, Burton V.; Blazer, Dan G.
Abstract : The coronavirus (COVID-19) pandemic is having profound effects on the lives and well-being of the world's population. All levels of the nation's public health and health care delivery systems are rapidly adjusting to secure the health infrastructure to manage the pandemic in the United States. As the nation's safety net health care systems, academic medical centers (AMCs) are vital clinical and academic resources in managing the pandemic. COVID-19 may also risk the financial underpinnings of AMCs because their cost structures are high, and they may have incurred large amounts of debt over the last decade as they expanded their clinical operations and facilities. This Invited Commentary reviews existing data on AMC debt levels; summarizes relief provided in the Coronavirus Aid, Relief, and Economic Security Act; and suggests policy options to help mitigate risk.